Estimation of Pulmonary Arterial Wave Reflection by Echo-Doppler: A Preliminary Study in Dogs With Experimentally-Induced Acute Pulmonary Embolism - Yoshida, Tomohiko; Uejima, Tokuhisa; Komeda, Syunta; Matsuura, Katsuhiro; Uemura, Akiko; Hayama, Hiromasa; Yamashita, Takeshi; Yilmaz, Zeki; Tanaka, Ryou (Frontiers in Physiology, 2021)
Background: Pulmonary arterial (PA) wave reflection provides additional information for assessing right ventricular afterload, but its applications is hampered by the need for invasive pressure and flow measurements. We tested the hypothesis that PA pressure and flow waveforms estimated by Doppler echocardiography could be used to quantify PA wave reflection. Methods: Doppler echocardiographic images of tricuspid regurgitation and right ventricular outflow tract flow used to estimate PA pressure and flow waveforms were acquired simultaneously with direct measurements with a dual sensor-tipped catheter under various hemodynamic conditions in a canine model of pulmonary hypertension (n=8). Wave separation analysis was performed on echo-Doppler derived as well as catheter derived waveforms to separate PA pressure into forward (Pf) and backward (Pb) pressures and derive wave reflection coefficient (RC) defined as Pb divided by Pf. Results: Wave reflection indices by echo-Doppler agreed well with corresponding indices by catheter (Pb: bias = 0.4 mmHg, 95% limits of agreement = -4.3 to 5.0 mmHg; RC: bias = 0.13, 95% limits of agreement = -0.25 to 0.26). RC correlated negatively with PA compliance. Conclusions: This echo-Doppler method yields accurate measurement of reflected wave in the pulmonary circulation, paving the way to a more integrative assessment of pulmonary hemodynamics in the clinical setting.